2018
DOI: 10.3389/fpsyg.2018.00442
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and Depression Affect Quality of Life in Patients With Chronic Pain: A Study on 205 Patients With Fibromyalgia

Abstract: Pain in fibromyalgia (FM) is accompanied by a heterogeneous series of other symptoms, which strongly affect patients’ quality of life and interfere with social and work performance. The present study aimed to evaluate the effects of alexithymia on both the physical and the psychosocial components of the health-related quality of life (HRQoL) of FM patients, controlling for the concomitant effects of depression, anxiety, and pain. In particular, given the strong interconnection between depression and alexithymi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 73 publications
4
42
0
3
Order By: Relevance
“…It is well known that depression and pain catastrophizing are two crucial psychosocial factors that influence the course and experience of chronic pain (Edwards et al ., ; Miller‐Matero, Chipungu, Martinez, Eshelman & Eisenstein, ; Morgan, ). Moreover, in contrast to the findings of a previous study performed with RA patients (Kojima et al ., ), but in agreement with a study performed with CP patients (Tesio et al ., ), the present regression analyses showed that also alexithymia significantly contributed to the explanation of both the physical and mental components of HRQoL.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…It is well known that depression and pain catastrophizing are two crucial psychosocial factors that influence the course and experience of chronic pain (Edwards et al ., ; Miller‐Matero, Chipungu, Martinez, Eshelman & Eisenstein, ; Morgan, ). Moreover, in contrast to the findings of a previous study performed with RA patients (Kojima et al ., ), but in agreement with a study performed with CP patients (Tesio et al ., ), the present regression analyses showed that also alexithymia significantly contributed to the explanation of both the physical and mental components of HRQoL.…”
Section: Discussionsupporting
confidence: 65%
“…Aside from psychological distress, a broad association between alexithymia and various chronic health problems has been suggested (Di Tella & Castelli, 2013;Kilic, Sar, Taycan et al, 2014;Sayar, Gulec & Topbas, 2004;Tesio, Di Tella, Ghiggia et al, 2018), but few studies have investigate the role of alexithymia in pain perception as well as depression in patients with RA (Donisan et al, 2017;Karahan, Kucuk, Balkarli et al, 2016;Kojima, Kojima, Suzuki et al, 2014). The prevalence of alexithymia among individuals with RA is around 22-31% (Karahan et al, 2016;Kojima et al, 2014), but is not clear if this trait can be considered as a strong predictor of health-related quality of life (HRQoL) (Donisan et al, 2017;Kojima et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Duygularını tanıma ve açıklamada zorlanan kişilerin fiziksel ve psikolojik belirtileri daha da artmakta ve kısır döngü içinde aleksitimik özellikleri besleyebilmektedir. 4 Aleksitimi duyguları tanıma ve açıklamada zorluk, fiziksel ve duygusal durumları ayırt edememe, hayal kurmada yetersizlik olarak tanımlanmıştır. 5 Çalışmalarda aleksitimik iletişim biçiminin başlangıçta psikosomatik hastalıklara özgü olduğu belirtilmişse de, günümüzde yalnızca bu hastalıklarda değil sağlıklı bireylerde de görüldüğü vurgulanmaktadır.…”
Section: Introductionunclassified
“…5 Çalışmalarda aleksitimik iletişim biçiminin başlangıçta psikosomatik hastalıklara özgü olduğu belirtilmişse de, günümüzde yalnızca bu hastalıklarda değil sağlıklı bireylerde de görüldüğü vurgulanmaktadır. 4,[6][7][8][9][10][11] Aleksitiminin ortaya çıkmasında sosyokültürel, kalıtsal ve çevresel faktörlerin etkili olduğu belirtilmektedir. Sosyoekonomik gelir seviyesi düşük olanlarda, kadınlarda ve ilerleyen yaşlarda aleksitimi görülme sıklığı artmaktadır.…”
Section: Introductionunclassified
See 1 more Smart Citation